Aplikasi Perancangan Kartu Tanda Siswa SMK YAPIM Pinang Awan Berbasis Web - Yanuar, Alfitra (Journal of Computer Science and Information System(JCoInS), 2023)
In this era of globalization computers are needed in all aspects of life except in the world of education. One student sign is the identity of students as students who are still actively participating in school education. Student identification cards obtained at the YAPIM Pinang Awan school include the process of designing student sign cards that is difficult, seems old and still manually using the Microsoft Word application. With the support of existing technology, data processing currently carried out can be replaced with a web-based system. Data collection methods used are observation, interview and literature study while the programming used is Web site programming using MYSQL and PHP databases. This research produces a web-based YAPIM Pinang Awan student card design application system. Hopefully with the application system the design of the student sign card can facilitate the making of student card / student card printing.